Diterpenoids from the whole plants of Croton yunnanensis and their bioactivities. (1st December 2021) - Su, Xiao-Min; Liang, Qian; Hu, Jia-Xin; Zhang, Xin-Min; Jia, Rong-Lin; Xu, Wen-Hui
Graphical abstract: Highlights: Five new diterpenoids, together with four known ones were isolated from whole plants of Croton yunnanensis . Their structures were elucidated on the basis of spectroscopic methods, and ECD calculations. Crotonyunnan E (5 ) exhibited selective cytotoxicities against three tumor cell lines, SMMC-7721 (IC50 4.47 ± 0.39 μM), HL-60 (IC50 14.38 ± 1.19 μM), and A-549 (IC50 27.42 ± 0.48 μM). Abstract: Four new 19-nor-clerodane diterpenoids (1 –4 ), one new 15, 16-dinor- ent -pimarane diterpenoid (5 ) together with four known diterpenoids (6 –9 ) were isolated from whole plants of Croton yunnanensis . The structures of these compounds were determined by extensive spectroscopic methods including 1D, 2D NMR, HR-ESI-MS, and by comparing their NMR data with those of previously reported compounds. The experimental and calculated electronic circular dichroism data were used to define their absolute configurations. The 1 H and 13 C NMR spectra of 6 were completely assigned for the first time. All isolated compounds (1 –9 ) were evaluated for their cytotoxic activities against five human cancer cell lines (including SMMC-7721, HL-60, A-549, MCF-7, and SW-480), and anti-inflammatory activities in LPS-induced RAW264.7 macrophages. Crotonyunnan E (5 ) exhibited selective cytotoxicities against three tumor cell lines, SMMC-7721 (human hepatoma cells, IC50 4.47 ± 0.39 μM), HL-60 (human premyelocytic leukemia, IC50 14.38 ± 1.19 μM), and A-549 (human lung cancer cells, IC50 27.42 ± 0.48 μM), while none of the compounds showed obviously anti-inflammatory activities at 50 μM level.